Implementasi Supervisi Manajerial Kepala Madrasah dalam Meningkatkan Kinerja Tenaga Administrasi - Taufan Taufan; Susi Yusrianti; Muhammad Anggung Manumanoso Prasetyo (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
This study aims to determine the implementation of managerial supervision by the madrasah head to improve the performance of administrative staff. The type of research used is qualitative with descriptive survey techniques. The data presentation is done using comparative analysis. Data from research conducted at MAS Ihyaaussunnah Lhokseumawe City. The results showed that the implementation of managerial supervision of the madrasah head could improve the performance of administrative staff. One of the successes of implementing managerial supervision is that the madrasah head conducts Islamic-based digitalization supervision. The various innovations made by the madrasah head are also a form of transformation of the managerial supervision implementation system in improving the performance of administrative staff. Implementation is carried out through several stages of managerial supervision carried out having commitment, directive functions, administrative supervision, performance improvement, providing solutions and self-reflection. The performance implications generated through this research are the performance of administrative staff as facilitators of academic services and learning evaluation, facilitators of teacher and staff data collection on emis, facilitators of student data collection on emis and student attendance, facilitators of madrasah facilities and inventory, facilitators of budgeting madrasah needs and reports on the use of BOS funds and facilitators of archives and madrasah files.